Students' Perception of Islamic Movies as an Instructional Media to Improve English Speaking Ability - Sri Wahyu Murni; Iis Sujarwati; Ari Andre Rianyansa (CV. Media Inti Teknologi, 2025)
Background: One of the most crucial language skills for learning English is speaking. Therefore, this study offers a different focus because it focuses on the students’ perceptions of and obstacles in using Islamic movies in English speaking class. this study is different from earlier research since a lot of current research uses classroom action research and quasi-experimental research. This study also differs from previous research that employed descriptive quantitative methods.Aims: The purpose of this study is to ascertain students' opinions regarding the use of Islamic movies as a teaching tool to enhance English speaking proficiency as well as the challenges associated with it.Methods: This study was carried out using a mixed-methods design. Purposive sampling was the sampling method used as a result. The interview and questionnaire were used as tools to address the study questions. The total population was 30 students from tenth grade. Only class A (30 students) was used as the sample for this study.Results: The findings indicated that the use of Islamic movies in English-speaking lessons was well received by the students. Some students, however, had various challenges when using it to speak English. These challenges included inadequate internet access, lacking elements in Islamic movies, language proficiency, and mental health issues.Conclusion: The researcher came to the conclusion that Hidayatul Mubtadi'ien Islamic Boarding School can effectively enhance English speaking skills through the use of Islamic movies.